How health-focused choirs adapted to the virtual world during the COVID-19 pandemic – An international survey. (February 2023) - Tamplin, Jeanette; Thompson, Zara
Abstract: The COVID-19 pandemic significantly impacted the operation of choirs around the world due to the high-risk nature of group singing for disease transmission. These risks are even greater for people living with health conditions. This paper presents the results of an international, cross-sectional survey that asked health-focused choir facilitators if and how they adapted their choir to due to COVID-19 restrictions and the high-risk of transmission during group singing. Participants were recruited through searches of choir and music therapy networks, social media, and snowballing sampling methods. The anonymous online survey consisted of 17 multiple choice and 7 short answer questions. Data was analysed using descriptive statistics and thematic analysis. Sixty-five surveys were commenced (50 completed). Many respondents (63 %) took their choirs online, and neurological conditions were the most common populations served. Format and methods of online choirs are described, as are benefits and challenges of online choirs. Several respondents indicated they would continue online post-COVID-19 restrictions. Online choirs were seen as feasible and beneficial, despite challenges. Recommendations regarding facilitator skills, technology set up, accessibility and session structure for online facilitation of health-focused choirs are provided. Highlights: Moving health-focused choirs online was a common approach during COVID-19 lockdowns. Online delivery of health-focused choir sessions is feasible, with benefits as well as challenges. Zoom is the preferred platform for online delivery of health-focused choirs. Recommendations for online facilitation of health-focused choirs are provided.